General Election 1945 - 'A call to the workers' (reverse) (1945)
1945 "General Election 1945 - 'A call to the workers' (reverse)" [T0371b.jpg], 1945 The TUC Election Manifesto, outlined its policies on reconstruction and full employment, public ownership, working hours and conditions, social security, scientific research into health and safety, education and the school leaving age and freedom of association. The document called on trade unionists and their families to give active support to Labour Party Candidates.